The role of habituation in the adjustment to urban life: An experimental approach with burrowing owls - Cavalli, Matilde (2018)
Birds exhibit variation in fear behaviour in response to an approaching human within and between species and across different habitat contexts. We analyze urban and rural burrowing owls’ variation in risk perception along separate but consecutive days (Treatment 1) and risk perception within the same day (Treatment 2). Fear behaviour was measured as flight initiation distances (FIDs) and aggressiveness level when a pedestrian approached repeatedly to an owl individual. We predict that the attenuation in fear response along treatments should add support to the habituation hypothesis (decrease the response to a repeatedly stimulus after verifying that it is irrelevant) while consistency in behaviour might be indicative of a personality trait. We found that FID decreased for measurements made on both treatments in rural owls and also in urban owls for Treatment 2. These results are compatible with a habituation process. We found that aggressiveness remained invariable along treatments in both habitats suggesting that different mechanisms underlie these behavioural responses. Our results suggest that owls’ risk perception to humans can be adjusted based on environmental risk perception and that individuals are able to recognize and learn when a stimuli stops being a threat.